Evaluation of periodontitis parameters and plaque examination by microscopy: a report on 20 patients - Mark Bonner (Frontiers Media S.A., 2024)
The protozoan parasite Entamoeba gingivalis has long been detected in diseased gingival pockets. The parasite is found in 81% of diseased sites using PCR and in up to 100% using microscopy, whereas it is mostly absent from healthy gingival sites. The purpose of this study on 20 periodontitis patients was to analyze the characteristic biofilm using phase-contrast microscopy and evaluate the results of a novel antiparasitic, anti-inflammatory therapeutical approach. The therapeutic strategy, termed "Periodontal Healing Protocol Bonner Dunoyé" (PHPBD), is implemented in monthly appointments for 8 months, and a control visit at one year. It involves a disinfection protocol, subgingival calculus removal, patient training and the microscopic analysis of periodontal biofilm sulci. The practitioner also records bleeding on probing (BOP) and pocket depth (PD) to quantify healing. In all cases, the initial biofilm composed mainly of parasites, neutrophils, spirochetes, and other motile bacteria was progressively replaced by a white blood cell-free biofilm, consisting of motionless coccoid bacteria, filaments, and epithelial cells, indicative of healthy periodontium. Results were stable from month 8 to month 12. At one year, both BOP and PD values were greatly reduced (96%-100% decrease) compared to initial levels. The average sulcus clinical pocket healing toward the 1-3 mm PD group teeth was close to 99% overall patients. In conclusion, implementation of PHPBD appears to result in complete healing of periodontitis within 12 months, as determined by BOP, PD, biofilm microscopic monitoring and elimination of motile bacteria, parasites, and inflammatory cells. Thus, periodontal dysbiosis can be microscopically guided toward predictable eubiosis. Further studies are needed to evaluate long-term benefits.